Comparison of water quality status of disturbed and undisturbed mangrove forest at Awat-Awat Lawas Sarawak - Gandaseca, Seca; Abd Wahab, Nur Liyana; Mohamad Pazi, Ahmad Mustapha; Rosli, Noraini; Hassan Zaki, Pakhriazad (Scientific Research Publishing, 2016)
Water quality testing was compulsory for management of safe and reliable water sources. Various sources of pollution and destruction of mangrove forest decrease the quality of river water. Thus a study was conducted to determine the water quality status of mangrove forest river water of Awat-Awat Lawas Sarawak and compare the water quality status of disturbed and undisturbed mangrove forest river in that area. Samples from twelve sampling stations were collected from both mangrove forest river from October 2013 to March 2014. In-situ data collected (pH, temperature, dissolved oxygen (DO), salinity, turbidity, total dissolved solid (TDS), conductivity) and laboratory analysis (biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (AN), total suspended solid (TSS)) were conducted according to the Standard method of Examination of Water and Wastewater AHPA 2005. Six water parameters: pH, DO, BOD, COD, AN and TSS value were used in calculating the Water Quality Index (WQI). Mean values for disturbed area were follows, pH (7.07), temperature (29.93°C), salinity (15.64 PSU), turbidity (55.13 NTU), DO (4.59 mg/L), BOD (0.73 mg/L), COD (10.16 mg/L), AN (0.14 mg/L), TSS (53.92 mg/L), TDS (23.14 mg/L) and conductivity (2.61 ms/m). Undisturbed area results were, pH (6.84), temperature (28.32°C), salinity (14.65 PSU), turbidity (35.41 NTU), DO (2.39 mg/L), BOD (0.55 mg/L), COD (15.82 mg/L), AN (0.13 mg/L), TSS (53.23 mg/L), TDS (22.82 mg/L) and conductivity (2.34 ms/m). There were no significant differences between two locations except for DO. Both water qualities of disturbed and undisturbed mangrove forest river were found under Class III, which describe that the water bodies are in moderate quality status.